Passive evaporative coolers for postharvest storage of fruit and vegetables: Where to best deploy them and how well do they perform - Defraeye, Thijs; Shoji, Kanaha; Schudel, Seraina; Onwude, Daniel; Shrivastava, Chandrima (Frontiers in Food Science and Technology, 2023)
Passive evaporative coolers have a huge potential to help smallholder farmers to preserve their fresh fruit and vegetables longer after harvest. However, we could benefit from more transparent information on where evaporative coolers perform sufficiently well to extend the postharvest life of the fresh produce significantly. Unsatisfactory evaporative cooler performance is a potential cause for farmers' limited adoption of this technology to reduce food losses. Our objective is to present easy-to-use tools that help to better scope regions with the best potential for direct passive evaporative coolers and for effectively deploying it. This information should help avoid installing evaporative coolers in areas with environmental conditions that only induce a temperature depression of a few degrees Celsius. Concretely, we developed design charts of the achievable temperature depression by evaporative cooling based on the local air temperature and humidity. We quantified for apple, banana, mango, and tomato the resulting additional days in postharvest life gained by storing the produce in an evaporative cooler. For these fruits, the gain in postharvest life using passive cooling is roughly 2–15 days for temperate climates with an ambient temperature of 20°C and a humidity of 50%. We present geographical maps of India, Nigeria, and the entire world at a 30 km resolution that answer how much evaporative cooling can maximally decrease the produce temperature and extend postharvest life for banana fruit. We found that passive evaporative cooling could induce up to a 7-day gain in postharvest life. We make these maps available online. We also quantify how well evaporative coolers perform concerning reducing the temperature and how they should be sized. Our results will facilitate installing evaporative coolers only in suitable regions. Our data also show in which months the cooler can be operated with the best performance. We thereby help avoid disillusion and loss of trust in the technology with smallholder farmers, policymakers, farmers, or farmer cooperatives. Further catalyzing the implementation of small-scale evaporative coolers can bring farmers significant gains in postharvest life, reduce food losses, and increase revenues.